Bio-efficacy of Essential Oil Extracted from Locally Available Orange (Citrus sinensis) Peels from Nepal - Poudel, Sujan; Bhatt, Bishan Datt (Journal of Nepal Chemical Society, 2024)
Essential oils from various plants are valued for their therapeutic, aromatic, antimicrobial, and antioxidant properties. The majority of them are employed in cleaning procedures, aromatherapy, stress reduction, food flavouring and preservation, and beauty products. The present investigation focuses on elucidating the chemical composition along with the antimicrobial and antioxidant properties of essential oil extracted from locally available orange (Citrus sinensis) peels, mainly exploring its bio-efficacy. The antibacterial property was studied against the gram-negative bacterium Escherichia coli and the gram-positive bacterium Bacillus subtilis. The analysis results revealed significant antimicrobial activity with zones of inhibition of 4 mm and 5.5 mm, respectively. The antifungal property was studied against the opportunistic pathogenic yeast Candida albicans, which showed positive activity, producing 4.5 mm of zone of inhibition. The antioxidant activity of the oil was determined using DPPH free radical scavenging assay, which showed an IC50 value of 1.3532 µL/mL. Qualitative phytochemical screening of the essential oil as determined using some standard colour-developing methods showed the presence of alkaloids, flavonoids, terpenoids, phenols, cardiac glycosides, and saponins. The above results were validated by FT-IR and GC/MS analysis. The FT-IR analysis revealed the presence of nitrogen-containing and oxygen-containing functional groups. The GC/MS analysis showed the presence of limonene, d-limonene, 1S-α-Pinene, 1R-α-Pinene, β-myrcene, linalool, α-humulene, α-terpineol, etc. These findings demonstrated that orange peels from Nepal that are readily available locally could be a source of compounds with antibacterial, antifungal, and antioxidant properties.